(2a+b+c)-(b+7a-c)=

Simple and best practice solution for (2a+b+c)-(b+7a-c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a+b+c)-(b+7a-c)= equation:


Simplifying
(2a + b + c) + -1(b + 7a + -1c) = 0

Remove parenthesis around (2a + b + c)
2a + b + c + -1(b + 7a + -1c) = 0

Reorder the terms:
2a + b + c + -1(7a + b + -1c) = 0
2a + b + c + (7a * -1 + b * -1 + -1c * -1) = 0
2a + b + c + (-7a + -1b + 1c) = 0

Reorder the terms:
2a + -7a + b + -1b + c + 1c = 0

Combine like terms: 2a + -7a = -5a
-5a + b + -1b + c + 1c = 0

Combine like terms: b + -1b = 0
-5a + 0 + c + 1c = 0
-5a + c + 1c = 0

Combine like terms: c + 1c = 2c
-5a + 2c = 0

Solving
-5a + 2c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2c' to each side of the equation.
-5a + 2c + -2c = 0 + -2c

Combine like terms: 2c + -2c = 0
-5a + 0 = 0 + -2c
-5a = 0 + -2c
Remove the zero:
-5a = -2c

Divide each side by '-5'.
a = 0.4c

Simplifying
a = 0.4c

See similar equations:

| Sen(4x)-cos(4x)=1 | | 12d+2=3d+74 | | 2-5b=2b-162 | | 6[x-2]=17.4 | | 8(v-1)=-16 | | 5[a+5]=62 | | 2-5b=2b-16 | | 33.8=6c+4 | | -58=2-6x | | 78=6(p-5)+6p | | 3e-6=11.7 | | 4[a+5]=36 | | 78=-6(p-5)+6p | | [1+ytan(xy)]dx+xtan(xy)dy=0 | | 15=2c-1 | | 29=5y+9 | | 2*x^2=32 | | y(x^2y^2-m)dx+x(x^2y^2+n)dy=0 | | h+169-8h=0 | | x^2-2mx-3=0 | | 24=6(w-2) | | 2-2sin^2(3x)=1 | | -3(8+x)+6x=-3 | | 2x-5y+9y= | | 1.280-2.5= | | -26.7+3.4*-0.3=4.4(-0.3-6) | | =16*-176 | | 4w+4x-12w+4w+9x+3y=x | | =16*(-176) | | 4w+4x-12w+4w+9x+3y= | | 5+x=6x-10 | | -4x+4=29+x |

Equations solver categories